2005
DOI: 10.1289/ehp.7635
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Biomarkers by Microarray Analysis of Peripheral Blood Mononuclear Cell Gene Expression in Benzene-Exposed Workers

Abstract: Benzene is an industrial chemical and component of gasoline that is an established cause of leukemia. To better understand the risk benzene poses, we examined the effect of benzene exposure on peripheral blood mononuclear cell (PBMC) gene expression in a population of shoe-factory workers with well-characterized occupational exposures using microarrays and real-time polymerase chain reaction (PCR). PBMC RNA was stabilized in the field and analyzed using a comprehensive human array, the U133A/B Affymetrix GeneC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 34 publications
3
70
0
1
Order By: Relevance
“…More importantly, linear regression revealed that the relationship between PF4 and CTAP-III was not markedly different when corrected for absolute platelet counts or any of the other measured white blood cell types. These results are an indication that the difference in serum levels of platelet-derived cytokines is not a simple reflection of the decrease in the absolute count of peripheral platelets or other blood cells, further corroborated by our recent observation that expression of PF4 RNA in peripheral blood mononuclear cells was consistently down-regulated in exposed individuals (mean decrease 58%) when compared with unexposed individuals (20).…”
Section: Discussionsupporting
confidence: 83%
“…More importantly, linear regression revealed that the relationship between PF4 and CTAP-III was not markedly different when corrected for absolute platelet counts or any of the other measured white blood cell types. These results are an indication that the difference in serum levels of platelet-derived cytokines is not a simple reflection of the decrease in the absolute count of peripheral platelets or other blood cells, further corroborated by our recent observation that expression of PF4 RNA in peripheral blood mononuclear cells was consistently down-regulated in exposed individuals (mean decrease 58%) when compared with unexposed individuals (20).…”
Section: Discussionsupporting
confidence: 83%
“…Further, a recent report from our study population showed a highly significant increase in IL-4R mRNA expression in peripheral mononuclear cells from benzene-exposed workers (31). The influence of benzene on the production and function of IL-10, IL-12, or VCAM1, and how benzene might alter stem, progenitor, or stromal cell responses to these compounds, is not known.…”
Section: Discussionmentioning
confidence: 61%
“…Gene expression biomarkers have also been explored in other areas, such as indicators of toxin exposure (Forrest et al, 2005) and longevity therapeutics (Spindler, 2006). In plants, DNA markers are routinely used in breeding applications to follow association and for the introgression of favorable gene alleles that impart desired agronomic traits (for review, see Collard and Mackill, 2008).…”
Section: Discussionmentioning
confidence: 99%